Sztereotípiák szerepe a bizonyítási eljárásban - Rácz, Nóra (Debreceni Jogi Műhely, 2012)
The aim of the study is to present the creation, development and forms of manifestation of the stereotype, furthermore, to represent how the certain created stereotypes influence the public thinking. The main trend of these ideas is to review whether the different stereotypical assumptions are shown in the course of demonstration and if yes, how they are emphatic. In addition to this I attempt to show how the generalizations gain ground in the criminal proceedings, especially in the demonstration. Prejudice will be examined from the aspect how the way of thinking of the adult population is pervaded by discrimination in Hungary today. My aim is to present how much the generalizations gain ground in the criminal proceedings, within this in the demonstration. In course of information and data collection I was led to the conclusion that in these days the stereotypes play very important role. In the course of my observations it became clearer and clearer to me that numerous stereotypes come round us. We think about different groups of people, things, situations, concepts in stereotypes. The range of stereotypes is quite wide. Stereotypes always have been and will be in human culture. We need them since they help to orientate in the world around us but they can be dangerous as well, since they can affect the minorities, genders and different groups of people disadvantageously. As I have already mentioned, the main trend is to reveal the criminal projection of prejudice. We have to deal with the stereotypes, we have to know them in order to be able to handle them. I am convinced that some kinds of stereotypes live in everyone, we think in stereotypes many times, even when we do not notice them. If the stereotypes extremely consolidate, stiffen, they can easily become prejudices hurting others. Prejudiced way of thinking hides very much danger, it is important to be aware of the prejudices existing in us and to try to get them over. From the point of view of the topic discrimination can realize in the course of arrest, demonstration, formal accusation and rendition of the judgement.